STRUKTUR DAN MAKNA UNDANG-UNDANG SULTAN ADAM PADA MASA KERAJAAN BANJAR KALIMANTAN SELATAN - Rustam Effendi (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2013)
This study aims to describe the backgrounds of the birth and meaning of Undangundang Sultan Adam (UUSA). It employed the hermeneutic method and philology. The data source was the UUSA text written in the era when Sultan Adam reigned over the Banjar Kingdom in 1825-1857. The findings are as follows. First, the birth of UUSA was due to the fight of two sects, i.e. ahlusunah waljamaah and ahlal albidaah. Second, the whole meaning of the UUSA text shows that: (1) the Banjar Kingdom was a theocratic kingdom, (2) ulemas and religious organizations played dominant roles in the government, (3) legal religious organizations were those in the Safii sect, (4) UUSA was written on the basis of the ideas of the ulema of the Banjar Kingdom, namely Haji Djamaloedin, and (5) UUSA aimed to serve as religious experience perfection, a guide for judges to make decisions, and an attempt to counter other religious organizations growing during the era.